2017
DOI: 10.1016/j.jconrel.2016.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 promiscuity is responsible for the immunostimulatory activity of nucleic acid nanocarriers

Abstract: Lipopolyamines (LPAs) are cationic lipids; they interact spontaneously with nucleic acids to form lipoplexes used for gene delivery. The main hurdle to using lipoplexes in gene therapy lies in their immunostimulatory properties, so far attributed to the nucleic acid cargo, while cationic lipids were considered as inert to the immune system. Here we demonstrate for the first time that di-C18 LPAs trigger pro-inflammatory responses through Toll-like receptor 2 (TLR2) activation, and this whether they are bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 94 publications
1
19
0
Order By: Relevance
“…The cationic lipids 209,204, 122,766 and 122,767 have similar or identical polar head group but shorter alkyl chains (12 or 14 carbon atoms) compared to the C18-lipopolyamine 120,525, 128,506 and 120,535 (Table 1). Differently from these C18-lipopolyamines, which activates only TLR2 [33], 209,204, 122,766 and 122,767 are able to activate both TLR2 and TLR4 HEK-transfected cells (Fig. 1B).…”
Section: The Mechanism Of Interaction Between Lipopolyamines and Tlrsmentioning
confidence: 93%
See 3 more Smart Citations
“…The cationic lipids 209,204, 122,766 and 122,767 have similar or identical polar head group but shorter alkyl chains (12 or 14 carbon atoms) compared to the C18-lipopolyamine 120,525, 128,506 and 120,535 (Table 1). Differently from these C18-lipopolyamines, which activates only TLR2 [33], 209,204, 122,766 and 122,767 are able to activate both TLR2 and TLR4 HEK-transfected cells (Fig. 1B).…”
Section: The Mechanism Of Interaction Between Lipopolyamines and Tlrsmentioning
confidence: 93%
“…1A) in a dose-dependent manner with an induction factor ranging from 2 to 4 compared to untreated cells. We previously showed that lipids 128,506, 120,535, 120,525 and 206,252 are activators of TLR2 ( [32,33] and Table 1). In order to identify the receptor involved in the immunostimulatory properties of lipids 122,766, 122,767 and 209,204, we investigated their ability to activate NF-κB in HEK293 cells transfected with an empty plasmid (w/o TLR) or encoding TLR2 or TLR4.…”
Section: The Studied Lipopolyamines Have Pro-inflammatory Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…56 The implication of contaminants or non-canonical pathways in those activations is a matter of controversy. 57 However, TLR4 and TLR2 are activated by sterile components such as Nickel ions 58 and synthetic cationic lipids, 59 or by HMGB1 protein that activates TLR2 or TLR4 depending on cellular type, 60 which excludes the involvement of contaminations and demonstrates the promiscuity of these TLRs. Here, the synthetic nature of 33-mer gliadin peptide and the use of Polymyxin B, rule out bacterial contamination and support our findings.…”
Section: Accepted Manuscriptmentioning
confidence: 99%